The Magic School Bus Gets Eaten : A Book About Food Chains - Relf, Patricia; Illustrated by Carolyn Bracken (New York Scholastic, 1996)
What could a tuna fish sandwich and some smelly green pond scum have in common? Come on an underwater adventure in the magic school bus and find out!
Include Color Illustrations
Keywords: Food chains (Ecology) -- Schools -- Marine ecology. -- Beaches